Common Agricultural Policy of the European Communities (Czech Journal of International Relations, 1992)
The author is aiming at a complex analysis of the present problems of the EC agricultural programs, which have become a social problem since the 1950's. The specific development of agriculture, peculiarities of its production and realization as well as the pressure and political forces of farmers have enforced an extensive system of state regulations. In individual stages of the EEC building -up, agriculture played an important role and the common agricultural policy and common market represent the most elaborate systems of economic integration. In the parallelism of state regulations (national agricultural policies) and supra-state reglementation (common agricultural policy), agriculture has reached significant success concerning its self-sufficiency, export as well as the modernization of production structures. Along with this development there have been problems in regards to the economic effectiveness of production, agricultural surplus and unbearable expenses of budget financing the common agricultural policy. Even conflicts with other world exporters, especially with the US., have come. The article has three parts. The first part ,,State and supra-state regulation of agriculture, EEC integration", engages in the causes of state interventions and in the creation of an institutional framework. The second part, "Mechanism of common agricultural market", analyzed the principles of functioning for integrated agriculture. The last part is devoted to the problems of a common agricultural policy balance and reform concerning intervention and protection systems.